Pengaruhikemampuan Kerja, Kompensasi, Dan Komitmen Kerja TerhadapiKinerja Pegawai (Studi Pada Pegawai CV Dewi Sri Rahma Kecamatan Gempol Kabupaten Pasuruan) - Siti Latifatul Mufidah; N. Rachma; Andi Normala (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
AbstractThis study aims to examine and explain work ability, compensation, work commitment to employee performance (study on employees of CV Dewi Sri Rahma, Gempol District, Pasuruan Regency). This research is an associative research type with a quantitative approach. The method used is a questionnaire. The sampling technique used the formula from Malhotra with the calculation results of 56 samples. To solve the problem in this study using SPSS assistance with validity test, reliability test, normality test, multiple linear regression analysis, multicollinearity test, heteroscedasticity test, F test, and t test. The results showed that simultaneously the variables of work ability, compensation, and commitment to employee performance. And there is a partial influence between the variables of work ability, compensation, and commitment to performance.. Keywords: ability, compensation, commitment, employee performance.